The emergence of pressure blade making : from origin to modern experimentation - Desrosiers, Pierre (Springer, 2020)
Human development is a long and steady process that began with stone tool making.nbsp; Because of this skill, humans were able to adapt to climate changes, discover new territories, and invent new technologies.nbsp; "Pressure knapping" isnbsp;the common term fornbsp;one methodnbsp;of creating stone tools, where a larger device or blade specifically made for this purpose is use to press out the stone tool.nbsp; Pressure knapping was invented in different locations and at different points in time, representing the adoption of the Neolithic way of life in the Old world...